Diversity and Evolution of Sensor Histidine Kinases in Eukaryotes. (25th September 2018) - Kabbara, Samar; Hérivaux, Anaïs; Dugé de Bernonville, Thomas; Courdavault, Vincent; Clastre, Marc; Gastebois, Amandine; Osman, Marwan; Hamze, Monzer; Cock, J Mark; Schaap, Pauline; Papon, Nicolas
Abstract: Histidine kinases (HKs) are primary sensor proteins that act in cell signaling pathways generically referred to as "two-component systems" (TCSs). TCSs are among the most widely distributed transduction systems used by both prokaryotic and eukaryotic organisms to detect and respond to a broad range of environmental cues. The structure and distribution of HK proteins are now well documented in prokaryotes, but information is still fragmentary for eukaryotes. Here, we have taken advantage of recent genomic resources to explore the structural diversity and the phylogenetic distribution of HKs in the prominent eukaryotic supergroups. Searches of the genomes of 67 eukaryotic species spread evenly throughout the phylogenetic tree of life identified 748 predicted HK proteins. Independent phylogenetic analyses of predicted HK proteins were carried out for each of the major eukaryotic supergroups. This allowed most of the compiled sequences to be categorized into previously described HK groups. Beyond the phylogenetic analysis of eukaryotic HKs, this study revealed some interesting findings: 1) characterization of some previously undescribed eukaryotic HK groups with predicted functions putatively related to physiological traits; 2) discovery of HK groups that were previously believed to be restricted to a single kingdom in additional supergroups, and 3) indications that some evolutionary paths have led to the appearance, transfer, duplication, and loss of HK genes in some phylogenetic lineages. This study provides an unprecedented overview of the structure and distribution of HKs in the Eukaryota and represents a first step toward deciphering the evolution of TCS signaling in living organisms.